2020
DOI: 10.1158/1078-0432.ccr-19-3487
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Expansion of Highly Functional Antigen-Specific T Cells from Patients with Melanoma by Nanoscale Artificial Antigen-Presenting Cells

Abstract: Schneck is entitled to a share of royalty received by the university on sales of products described in this article. He is also a founder of NexImmune and owns equity in the company and he serves as a member of NexImmune's Scientific Advisory Board. The terms of these arrangements have been reviewed and approved by The Johns Hopkins University in accordance with its conflict of interest policies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Noteworthy is that starting leukapheresis material contains a large population of naïve T cells on day 0 (∼21%), while the final product contains on average less than 3% naïve T cells, as shown in Figure 4A. Furthermore, as demonstrated by Ichikawa et al [18], similar memory cell populations and subtypes are also produced from relapsed refractory melanoma patients when compared to healthy donors. Thus, this AIM-np-based approach reproducibly manufactures T-cell products that have the desired combination of memory phenotypes that have the potential to mediate an effective and long-lasting anti-tumor response.…”
Section: In Vitro Characterization Of Aim-expanded T-cell Productsmentioning
confidence: 83%
See 1 more Smart Citation
“…Noteworthy is that starting leukapheresis material contains a large population of naïve T cells on day 0 (∼21%), while the final product contains on average less than 3% naïve T cells, as shown in Figure 4A. Furthermore, as demonstrated by Ichikawa et al [18], similar memory cell populations and subtypes are also produced from relapsed refractory melanoma patients when compared to healthy donors. Thus, this AIM-np-based approach reproducibly manufactures T-cell products that have the desired combination of memory phenotypes that have the potential to mediate an effective and long-lasting anti-tumor response.…”
Section: In Vitro Characterization Of Aim-expanded T-cell Productsmentioning
confidence: 83%
“…3B). In a separate study comparing specificity, phenotype, and functionality of T-cell products, Ichikawa et al [18] have shown that the AIM-np based E+E process generates Mart-1-specific T-cell products from both healthy donors and melanoma patients that are far superior to T-cell products that were generated with peptide-loaded autologous DCs. As antigen-specific T cells are enriched from the endogenous T-cell repertoire, donor-to-donor variability will affect final composition of the product.…”
Section: Antigen Specificity Of Aim-expanded T-cell Productsmentioning
confidence: 99%
“…The efficacy of aAPCs could be improved by modifying the nanoparticle morphology 182 , signal coupling 183 , and fluidity 136 . Further exploration and establishment of protocols of aAPCs with personalized neoantigens may generate highly effective and personalized tumor vaccines 184 , 185 . In a recent study, the immune response of autologous tumor antigen was enhanced by a hybrid membrane delivery strategy 77 .…”
Section: Nanovaccines For Diseases Prevention and Treatmentsmentioning
confidence: 99%
“…Micro- and nanomaterial-based artificial APCs (aAPCs) are designed to mimic the natural APCs by presenting important signal antigens to T cells and activate them for cancer inhibition. 136 , 137 To realize these antigen-presenting effects, aAPCs should include two parts on their surface: MHC-peptide complexes that can present cognate antigenic peptide to T cell receptors and co-stimulatory molecules that can bind to co-stimulatory receptors and activate T cells. Compared with natural DCs, aAPCs have a relatively defined composition and controllable biological behavior.…”
Section: Harnessing Peripheral Immune Cellsmentioning
confidence: 99%